Public Interest vs. Interest Groups: Allowance Allocation in the EU Emissions Trading Scheme - Niels Anger; Christoph Böhringer; Ulrich Oberndorfer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper presents a political-economy analysis of allowance allocation in the EU Emissions Trading Scheme (EU ETS). A common-agency model suggests that a politicalsupport maximizing government considers the preferences of sectoral interest groups besides public interest when allocating emissions permits. In the stylized model, industries represented by more powerful lobby groups face a lower regulatory burden, which for sufficiently high lobbying power leads to an inefficient emissions regulation. An empirical analysis of the first trading phase of the EU ETS corroborates our theoretical prediction for a cross-section of German firms, but also shows that the political-economy determinants of permit allocation depend on firm characteristics. We find that large carbon emitters that were heavily exposed to emissions regulation and simultaneously represented by powerful interest groups received higher levels of emissions allowances. In contrast, industrial lobbying power stand-alone or threats of potential worker layoffs did not exert a significant influence on the EU ETS allocation process.
Keywords: P16; Q58; C10; 330; Emissions trading; interest groups; regression analysis; Emissionsrechte; Allokation; Interessenpolitik; EU-Staaten